What do patients and informal caregivers value in IBD care? A narrative inquiry - Britt J.M. Thomassen; Evelien M.B. Hendrix; Zlatan Mujagic; Fabiënne G.M. Smeets; Marin J. de Jong; Tom J.G. Gevers; Govert Veldhuijzen; Daniëlle van der Horst; Menne Scherpenzeel; Gerard Dijkstra; Merel L. Kimman; Stephanie M.C. Ament; et al. (BMC Health Services Research)
Abstract Background Inflammatory Bowel Disease (IBD) is an increasingly prevalent chronic condition that impacts the lives of patients and their relatives, and burdens healthcare systems. Redesigning care processes is warranted, with digital technologies offering opportunities to increase efficiency and reduce workloads. However, successful innovations require meaningful involvement of patients and informal caregivers. In this study, we aimed to identify what IBD patients and their informal caregivers value in IBD care. Methods A purposive sample of 18 IBD patients and 8 informal caregivers was drawn from an academic and a non-academic hospital in the Netherlands. Semi-structured interviews with a narrative approach focused on capturing real-life experiences and personal stories related to IBD care. Transcripts were analysed using inductive thematic analysis. Results Patients and informal caregivers valued clear information and support regarding the disease, treatment, and daily management, along with active involvement in treatment planning. Regular contact with the same trusted healthcare professionals (HCPs), and effective treatment that alleviates symptoms and enables normal living, were deemed important. Patients appreciated a holistic, personalized approach. They welcomed remote care for follow-up and self-management, as long as the remote monitoring program was trustworthy and included easily accessible outpatient care if needed. Informal caregivers valued attentive HCPs who take patients seriously. Conclusions Key elements of IBD care valued by patients and informal caregivers include comprehensive support, active involvement, a person-centred approach, easy access to outpatient care, regular follow-ups with trusted HCPs, and remote care complementing outpatient services. Innovation teams should consider these elements when refining and developing innovations in IBD care.